2000
DOI: 10.1177/002215540004800111
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin Is Expressed in Normal and Pathological Human Parathyroid Glands

Abstract: SUMMARYThe parathyroid glands are of major importance in calcium homeostasis. Small changes in the plasma calcium (Ca 2 ϩ ) concentration induce rapid changes in parathyroid hormone (PTH) secretion to maintain the extracellular Ca 2 ϩ levels within the physiological range. Extracellular Ca 2 ϩ concentration is continuously measured by a G-proteincoupled Ca 2 ϩ -sensing receptor, which influences the expression and secretion of PTH. The mechanism of signal transduction from receptor sensing to PTH secretion is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…The distribution of parvalbumin in the kidney matches fairly well that of calcium receptors in the distal tubule and in the proximal collecting duct, where the fine regulation of calcium readsorption takes place (32,33). It is of interest that parathyroid glands possess the same calcium receptor found in the kidney, and a recent report has shown that parvalbumin, but not calbindin-D28K and calretinin, is expressed in parathyroid cells (31). The characteristic presence of parvalbumin in both chromophobe carcinoma and parathyroid cells raises the questions of its potential role as a modulator of calcium signals within chromophobe neoplastic cells of the distal nephron involved in calcium homeostasis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The distribution of parvalbumin in the kidney matches fairly well that of calcium receptors in the distal tubule and in the proximal collecting duct, where the fine regulation of calcium readsorption takes place (32,33). It is of interest that parathyroid glands possess the same calcium receptor found in the kidney, and a recent report has shown that parvalbumin, but not calbindin-D28K and calretinin, is expressed in parathyroid cells (31). The characteristic presence of parvalbumin in both chromophobe carcinoma and parathyroid cells raises the questions of its potential role as a modulator of calcium signals within chromophobe neoplastic cells of the distal nephron involved in calcium homeostasis.…”
Section: Discussionmentioning
confidence: 57%
“…It can act as a cytosolic calcium ion buffer, but a possible indirect role in signal transduction by modifying calcium concentration has been proposed (31). The distribution of parvalbumin in the kidney matches fairly well that of calcium receptors in the distal tubule and in the proximal collecting duct, where the fine regulation of calcium readsorption takes place (32,33).…”
Section: Discussionmentioning
confidence: 94%
“…15,16 Similarly, parvalbumin, a calcium-binding protein with a major role in calcium homeostasis, is detected in many metabolically active cell types such as muscle, neuron, and endocrine glands as well as their related tumors. 17,18 In contrast, Ksp-cadherin, is limited to the kidney. Previous immunohistochemical and Northern hybridization studies have failed to show its expression in other organs including lung, prostate, pancreas, skin, muscle, liver, stomach and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…PV immunoreactivity was also observed in several other endocrine glands like ovaries, pituitary, thyroid, parathyroid, and adrenal glands, which suggests an important role for PV in endocrine secretions. (15,89,90) Studies are in progress to elucidate the different physiological roles of these Ca 2þ -binding proteins in the testis, which may provide a better understanding of Leydig cell activity and spermatogenesis. Additionally, PV may also serve as a diagnostic tool in revealing testicular disorders during development.…”
Section: Pv Plays a Role In Endocrine Regulationmentioning
confidence: 99%